Use of Primary Amines for the Selective N-Alkylation of Anilines by a Reusable Heterogeneous Catalyst - Linciano, Pasquale; Pizzetti, Marianna; Porcheddu, Andrea; Taddei, Maurizio (Synlett, 2013)
Traditionally, anilines can be alkylated with reactive alkyl halides but now more safe reagents such as alcohols or even amines can be used. To overcome the limits of homogeneous catalysis for aniline N-alkylation, we have developed a protocol that employs simple Pd/C as a heterogeneous catalyst under microwave dielectric heating. The process, based on the easy Pd-mediated oxidation of primary amines to imines followed by aniline addition, is characterized by a high atom economy as ammonia is the only other product of the reaction. This kind of aniline alkylation with amines has been carried out both in ionic liquid medium using [bmim]PF6 or in a more traditional solvent such as THF where the catalyst could be successfully recycled more times. The reusability of the catalyst was further confirmed by using material recycled from the amination in a standard alkene hydrogenation without loss of efficiency.
Keywords: hydrogen transfer; microwave chemistry; oxidation; amination; palladium